2011
DOI: 10.2196/jmir.1614
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Guide to Health: Relationship of Theoretical Variables to Change in Physical Activity, Nutrition and Weight at 16-Months

Abstract: BackgroundEvaluation of online health interventions should investigate the function of theoretical mechanisms of behavior change in this new milieu.ObjectivesTo expand our understanding of how Web-based interventions influence behavior, we examined how changes at 6 months in participants’ psychosocial characteristics contributed to improvements at 16 months in nutrition, physical activity (PA), and weight management as a result of the online, social cognitive theory (SCT)-based Guide to Health intervention (WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 31 publications
(53 reference statements)
0
48
3
3
Order By: Relevance
“…Social media has been considered as a means to disseminate health information [2,6] and as a way to provide online social support for health issues [3,28,59]. Mental health is traditionally stigmatised by society [4], meaning that those suffering from such illness may find it harder to disclose details of their disorders [21].…”
Section: Introductionmentioning
confidence: 99%
“…Social media has been considered as a means to disseminate health information [2,6] and as a way to provide online social support for health issues [3,28,59]. Mental health is traditionally stigmatised by society [4], meaning that those suffering from such illness may find it harder to disclose details of their disorders [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Anderson-Bill et al tested whether SCT constructs were predictive of PA behavior in an online, SCT-based intervention program known as Guide to Health . The authors demonstrated that program user's perceived social support, use of self-regulatory behaviors, and self-efficacy were predictive of physical activity levels (Anderson-Bill, Winett, & Wojcik, 2011), and in a longitudinal model, improvements in the same constructs strongly predicted improved PA levels (Anderson-Bill, Winett, Wojcik, & Winett, 2011). This work illustrates the importance of identifying Internet features that are both appealing to users and based on theoretical constructs known to predict PA behavior (Hawkins, Kreuter, Resnicow, Fishbein, & Dijkstra, 2008; van den Berg et al, 2007).…”
mentioning
confidence: 99%
“…Além dos construtos elencados na primeira coluna do Quadro 1, como "determinantes psicossociais", mencionam também preferências alimentares (Anderson-Bill et al, 2011;Tuuri et al, 2009;Van Duyn et al, 2001), resiliência (Clark et al, 2011), depressão (Clark et al, 2011;Zemper et al, 2003), problemas de ajustamento relacionados a perdas no trabalho e casamento e satisfação com a vida (Zemper et al, 2003). Um dos artigos mencionava aferição de fatores psicossociais em seu resumo, sem maior detalhamento (Rimmer et al, 2000).…”
Section: A Literatura Sobre Promoção De Práticas Alimentares Saudáveisunclassified
“…Os trabalhos de intervenção analisados podem também ser categorizados de acordo com o seu alcance e modalidade: intervenções individuais que utilizam estratégias de promoção da saúde realizadas a distância, por computador, correio e/ou telefone (Anderson-Bill et al, 2011;Robroek et al, 2010;Elder et al, 2009;Portnoy et al, 2008;Van Keulen et al, 2008;Van Duyn et al, 2001), intervenções face a face realizadas com grupos específicos (Clark et al, 2011;Bonnel, 2003;Zemper et al, 2003;Langenberg et al, 2000;Rimmer et al, 2000), intervenções com base na família ou escola (Chen et al, 2010;Pearson et al, 2010;Goh et al, 2009;Tuuri et al, 2009;Burgess-Champoux et al, 2008;Haerens et al, 2008;Saksvig et al, 2005;Verheijden et al, 2003;Parcel et al, 2003) e, finalmente, intervenções de base comunitária (Gittelsohn et al, 2010;Mead et al, 2010;Campbell et al, 2007 Benefícios percebidos: opinião quanto à eficácia da ação aconselhada na redução de riscos para a saúde.…”
Section: A Literatura Sobre Promoção De Práticas Alimentares Saudáveisunclassified
See 1 more Smart Citation